Glioblastoma Microenvironment: From an Inviolable Defense to a Therapeutic Chance - Di Nunno, Vincenzo; Franceschi, Enrico; Tosoni, Alicia; Gatto, Lidia; Bartolini, Stefania; Brandes, Alba Ariela (Frontiers in Oncology, 2022)
Glioblastoma is an aggressive tumor and is associated with a dismal prognosis. The availability of few active treatments as well as the inexorable recurrence after surgery are important hallmarks of the disease. The biological behavior of glioblastoma tumor cells reveals a very complex pattern of genomic alterations and is partially responsible for the clinical aggressiveness of this tumor. Recently, it has been observed that glioblastoma cells are able to recruit, manipulate and use other cells including neurons, glial cells, immune cells, and endothelial/stromal cells. The final result of this process is a very tangled net of interactions promoting in glioblastoma growth and progression. Nonetheless, there are very recent data suggesting that the microenvironment can also be a niche in which glioblastoma cells can differentiate into glial cells losing their clinical aggressive features. Here we summarize the known interactions between micro-environment and glioblastoma cells highlighting possible therapeutic implications.